The Effect of Asset Encumbrance on Bank Behavior: Evidence from the Introduction of Covered Bonds in Norway - Cao, Jin; Juelsrud, Ragnar; Sondershaus, Talina (Journal of the European Economic Association, 2025)
We use the introduction of covered bonds in Norway in 2007 together with administrative and supervisory data at the bank and loan level to investigate the effect of asset encumbrance, that is, pledging assets as collateral, on the composition of bank balance sheets and bank risk. We show that covered bonds—despite being collateralized with mortgages—lead to a shift in bank lending from mortgages to corporate loans. The marginal corporate borrower is young and low-rated, suggesting that overall credit risk increases. At the same time, we find that balance sheet liquidity increases. Overall, the beneficial effects of increased liquidity on bank risk outweighs any negative effects of increased credit risk, ultimately reducing risk premia on total and unsecured funding. The effects are driven by banks with initially low net holdings of liquid assets and low firm credit risk in their lending portfolios.